The analgesic efficacy of pericapsular nerve group block in patients with intertrochanteric femur fracture: A randomized controlled trial - Kong, Mingjian; Tang, Yan; Tong, Fei; Guo, Hui; Zhang, Xin Lei; Zhou, Lei; Ni, Hua; Wang, Bin; Liu, Yunqing; Liu, Jindong (PloS one, 2022)
The aim of this study is to evaluate analgesic efficacy of pericapsular nerve group (PENG) block in patients with intertrochanteric femur fracture (IFF). This double-blinded randomized controlled trial in patients with IFF scheduled for proximal femoral nail antirotation (PFNA) between December 2020 and November 2021. The primary outcome was VAS scores during exercising at 6 h after surgery; secondary outcomes were pain during exercising and rest, intraoperative dose of remifentanil, cumulative dose of postoperative fentanyl, postoperative analgesia satisfaction scores, and ratio of quadriceps weakness. A total of 50 patients were randomly divided into PENG block group (n = 25) or fascia iliaca compartment block (FICB) group (n = 25). Exercising VAS scores at 6 h after surgery were significantly lower in PENG block group than that in FICB group (2 (2, 4) vs. 6 (4, 7), P < 0.001). The intraoperative dose of remifentanil and cumulative dose of postoperative fentanyl by patient-controlled intravenous analgesia within 24 h after surgery in PENG block group were significantly lower than in FICB group (both P < 0.001). Postoperative analgesia satisfaction scores in PENG block group were significantly higher than those in FICB group (P = 0.016). The ratio of quadriceps weakness at 6 h after surgery was significantly higher in FICB group than PENG block group (48% vs. 0%, P < 0.001). Compared to FICB, ultrasound-guided PENG block may provide better postoperative pain relief in patients with IFF, with less pronounced quadriceps weakness.